A Case Study on the Evaluation of WhatsApp Groups Established for Managerial Purposes by Academicians - Onur Doğan; Alev Elçi; Zeliha Seçkin (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Technological developments have enabled the traditional nature of communication to evolve into digital messaging. These developments gained momentum amid the COVID-19 process and brought instant messaging and social media communication to the forefront. WhatsApp, one of the most commonly used instant messaging applications for informal communication, has also started being favored more for formal communication in organizational management. WhatsApp has become a powerful professional communication tool that organizational administrators preferred, has become to serve organizational purposes as an alternative to formal information and document sharing platforms. This study aims to investigate whether WhatsApp messaging effectively serves organizational purposes in higher education, and evaluates how it is perceived and utilized by academicians. This case study is a type of qualitative research where the data collected from the workgroup are analyzed by descriptive analysis to obtain findings. Five main themes are derived from the analysis; namely group structure and characteristics, communication, cooperation, psycho-social impact, negative opinions, and related ten sub-themes were detected. According to the results derived from the study, most of the participants expressed mostly positive and some negative perceptions regarding the communication made through the WhatsApp groups established for administrative purposes.